PEMANFAATAN LIMBAH KULIT UDANG SEBAGAI BAHAN BAKU PEMBUATAN MEMBRAN ULTRAFILTRASI - Kusumawati, Nita (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2009)
AbstractThis research was aimed to study the made of chitosan membrane.The chitosan membrane was made from industrial waste of prawn packingfactory. The prawn husk was extracted to become chitin before it was thentransformed to chitosan. In order to make a membrane, the chitosan wasmixed with an acetic acid solution using magnetic stirrer. The mixed ofchitosan and an acetic acid solution was doing for 24 hour to make sure thesolution are homogenic. After that, chitosan solution was stored to glassplate 10x10 cm. The glass plate that have been with chitosan solution thendried for 48 hours. A Chitosan Membrane that have made was keeped withthe plate until it used.Keywords: chitosan membrane, industrial waste